Research Progress of Nerve Mobilization in Basic and Clinical Rehabilitation - Shuo LUAN; Quanshou LING; Miaoshang ZENG; Anni LIN; Yingping JIANG (康复学报)
The purpose of this paper is to provide a systematic review of the literature concerning the theoretical basis, research advance and clinical status of nerve mobilization(NM)in various neuro-musculoskeletal conditions, which may provide important information for future medical studies. The NM technique is developed based on anatomy, biomechanics, and neurodynamics, and the treatment is applied by stretching and relaxing the specific nerve tissues with appropriate power at the desired direction. By improving the neural tension, axoplasmic transport and the issue microenvironment, the NM helps the anatomical structure and physiological function of nerve tissues restore to normal condition. The two main types of neurodynamic techniques are"sliding technique"and"tensioning technique"respectively. The"sliding technique"results in the relative large longitudinal excursion of nerve with a minimal increase of strain, thus it seems less aggressive than"tensioning technique"and might be more appropriate for acute injuries at the early stage. While the"tensioning technique"usually leads to significant changes in nerve tension to increase the distance between each end of the nerve tract and prevent tissue adhesion during the convalescence period. For the symptomatic patients, the changes of mechanical tension and movement sequence should be identified before the individualized NM treatment. Recent years, the NM technique has been widely used in peripheral nerve entrapment syndromes, periphery nerve injuries, and stroke rehabilitation. The NM technique facilitates to reduce intraneural edema, inflammation response and nerve root irritation. Besides, the NM technique also plays an important role in the postoperative rehabilitation of peripheral nerve injury, since the edema, tissue adhesion and reduced blood flow could influence curative effects and surgical prognosis in negative ways. Preliminary evidences suggest that metabolic and endocrine diseases generally involve the neural disorders and the NM is beneficial for treating the symptomatic diabetic peripheral neuropathy. Despite of insufficient evidence, the NM is proved to be used in the prevention, assessment and treatment of neurological disorders, including stroke, traumatic brain injury and Parkinson's disease. Moreover, previous studies proved that peripheral mechanical loads applied to neural tissues could improve the central neural plasticity, and the improvements were observed in muscular tone, strength, body weight distribution, postural balance and other functional motor performances, which helped to attenuate the motor dysfunction of the upper and lower limbs. Future studies are necessary to validate the treatment frequency, treatment duration and movement sequence for varies diseases and physiopathological conditions. To our knowledge, there are still few qualified clinical randomized controlled trials(RCT)and system reviews about the therapeutic effects of NM techniques, especially the in-depth explorations at the molecular and genetic levels. Up till now, the positive observed effects of NM technique are mainly based on anecdotal evidences. The curative effects and related mechanisms, including anti-inflammation, increased axonal transport efficiency and nerve tissue regeneration deserve more future investigations. The long-term randomized trials with large samples are needed to observe and identify the therapeutic effects sustained over-time.